Physicochemical and nutritional properties of jussara pulp powder (Euterpe edulis M.) by spray-drying (Research, Society and Development, 2021)
The jussara palm (Euterpe edulis) is well known for its great presence in several Brazilian states and produces an edible palm heart and spherical fruits popularly known as jussara. Due to their high anthocyanin content, these fruits contain only one light brown seed that is covered by thin and dark purple skin.  This study was carried out to evaluate the effects of different mixtures of carrier agents (CA) (modified starch-MS plus whey protein concentrate-WPC or soy protein isolate-SPI) on the characteristics of microcapsules containing spray-dried jussara pulp powder. Four treatments, 30%CAC+17.5%MS:WPC, 17.5%CAC+30%MS:WPC, 30%CAC+17.5%MS:SPI and 17.5%CAC+30%MS:SPI, were evaluated, where CAC=carrier agent concentration (g carrier/g jussara pulp solids) and the proportions MS:WPC and MS:SPI indicate the grams of protein (WPC or SPI) per 100g of carrier. The concentration of 30%CAC+17.5%MS:WPC improved the wettability, anthocyanin content, total phenolic content and encapsulation efficiency. The particles presented smoother surfaces with a reduced number of folds when WPC was present. The usage of WPC or SPI mutually with MS was shown as a valid option in the spray drying of jussara pulp.